Influenza vaccines for preventing cardiovascular disease - Clar, Christine; Oseni, Zainab; Flowers, Nadine; Keshtkar-Jahromi, Maryam; Rees, Karen (São Paulo Medical Journal, 2015)
BACKGROUND: This is an update of the original review published in 2008. The risk of adverse cardiovascular outcomes is increased with influenza-like infection, and vaccination against influenza may improve cardiovascular outcomes. OBJECTIVES: To assess the potential benefits of influenza vaccination for primary and secondary prevention of cardiovascular disease. METHODS: Search methods: We searched the following electronic databases on 18 October 2013: The Cochrane Library (including Cochrane Central Reg-ister of Controlled Trials (CENTRAL), Database of Abstracts of Reviews of Effects (DARE), Economic Evaluation Database (EED) and Health Tech-nology Assessment database (HTA)), MEDLINE, EMBASE, Science Cita-tion Index Expanded, Conference Proceedings Citation Index – Science and ongoing trials registers (www.controlled-trials.com/ and www.clini-caltrials.gov). We examined reference lists of relevant primary studies and systematic reviews. We performed a limited PubMed search on 20 February 2015, just before publication. Selection criteria: Randomised controlled trials (RCTs) of influenza vac-cination compared with placebo or no treatment in participants with or without cardiovascular disease, assessing cardiovascular death or non-fatal cardiovascular events. Data collection and analysis: We used standard methodological pro-cedures as expected by The Cochrane Collaboration. We carried out meta-analyses only for cardiovascular death, as other outcomes were reported too infrequently. We expressed effect sizes as risk ratios (RRs), and we used random-effects models. MAIN RESULTS: We included eight trials of influenza vaccination com-pared with placebo or no vaccination, with 12,029 participants receiv-ing at least one vaccination or control treatment. We included six new studies (n = 11,251), in addition to the two included in the previous version of the review. Four of these trials (n = 10,347) focused on pre-vention of influenza in the general or elderly population and reported cardiovascular outcomes among their safety analyses; four trials (n = 1682) focused on prevention of cardiovascular events in patients with established coronary heart disease. These populations were analysed separately. Follow-up continued between 42 days and one year. Five RCTs showed deficits in at least three of the risk of bias criteria assessed. When reported (seven studies), vaccination provided adequate immu-nogenicity or protection against influenza. Cardiovascular mortality was reported by four secondary prevention trials and was significantly reduced by influenza vaccination overall (risk ratio (RR) 0.45, 95% confi-dence interval (CI) 0.26 to 0.76; P value 0.003) with no significant hetero-geneity between studies, and by three trials reporting cardiovascular mortality as part of their safety analyses when the numbers of events were too small to permit conclusions. In studies of patients with coro-nary heart disease, composite outcomes of cardiovascular events tend-ed to be decreased with influenza vaccination compared with placebo. Generally no significant difference was found between comparison groups regarding individual outcomes such as myocardial infarction. AUTHORS’ CONCLUSIONS: In patients with cardiovascular disease, in-fluenza vaccination may reduce cardiovascular mortality and combined cardiovascular events. However, studies had some risk of bias, and re-sults were not always consistent, so additional higher-quality evidence is necessary to confirm these findings. Not enough evidence was avail-able to establish whether influenza vaccination has a role to play in the primary prevention of cardiovascular disease.